Fondasi Mariologis dari Peranan Maria dalam Kerasulan Legio Maria - Pasi, Gregorius; Selamat , Shelomita (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2026)
On the one hand, Marian devotion is an integral part of the Catholic faith. On the other hand, the apostolate is part of the very nature of the Church's vocation. In practice, the correlation between the two is often overlooked. Marian devotion and other forms of religious devotion should have implications on the apostolate. The faithful need to be helped to discover the implications of their Marian devotion (and other forms of devotion) on the apostolate. To that end, It is necessary to provide examples of how marian devotion influences the apostolate. One lay apostolate group founded on marian devotion is the Legion of Mary. In the Legion's apostolate, Mary plays a role. This study aims to articulate the mariological foundations of Mary's role in the apostolate of the Legion of Mary. Before articulating the mariological foundation, it is necessary to first articulate Mary's role in the apostolate of the Legion of Mary. In articulating these two points, we use a qualitative approach, specifically a critical analysis of relevant documents. After that, we theologize about Mary's role in the apostolate of the Legion of Mary using classical theological methods. We find three roles for Mary in the apostolate of the Legion of Mary, namely leader, example and mediator of all graces. These three roles are mariologically based on Mary’s maternal role over humanity in the order of grace. Mary’s maternal role over humanity is an extension of her maternal role over Jesus.